Increased Arctic sea ice drift alters adult female polar bear movements and energetics. (6th June 2017) - Durner, George M.; Douglas, David C.; Albeke, Shannon E.; Whiteman, John P.; Amstrup, Steven C.; Richardson, Evan; Wilson, Ryan R.; Ben‐David, Merav
Abstract: Recent reductions in thickness and extent have increased drift rates of Arctic sea ice. Increased ice drift could significantly affect the movements and the energy balance of polar bears ( Ursus maritimus ) which forage, nearly exclusively, on this substrate. We used radio‐tracking and ice drift data to quantify the influence of increased drift on bear movements, and we modeled the consequences for energy demands of adult females in the Beaufort and Chukchi seas during two periods with different sea ice characteristics. Westward and northward drift of the sea ice used by polar bears in both regions increased between 1987–1998 and 1999–2013. To remain within their home ranges, polar bears responded to the higher westward ice drift with greater eastward movements, while their movements north in the spring and south in fall were frequently aided by ice motion. To compensate for more rapid westward ice drift in recent years, polar bears covered greater daily distances either by increasing their time spent active (7.6%–9.6%) or by increasing their travel speed (8.5%–8.9%). This increased their calculated annual energy expenditure by 1.8%–3.6% (depending on region and reproductive status), a cost that could be met by capturing an additional 1–3 seals/year. Polar bears selected similar habitats in both periods, indicating that faster drift did not alter habitat preferences. Compounding reduced foraging opportunities that result from habitat loss; changes in ice drift, and associated activity increases, likely exacerbate the physiological stress experienced by polar bears in a warming Arctic. Abstract : To compensate for greater westward and northward sea ice drift between 1987–1998 and 1999–2013, polar bears in the Beaufort and Chukchi seas increased their time active (8.1%–9.6%) or travel speeds (8.5%–8.9%). This increased their annual energy expenditures by 1.8%–3.6%, which could be met by capturing an additional 1–3 seals/year.